The Evolvement of Classical Arabic?: Linguistic study in Jordanian Dialects’ Phenomena - Alzu’bi, معاذ; Al-Osaily, إياد فتحي; Shalan, سناء كامل; Al-Shawabkeh, سمية سليمان (Dirasat: Human and Social Sciences, 2023)
Objectives: This research delves into phenomena in the diverse Jordanian Arabic dialect, situated in a geographically significant area historically linked to the Roman State. Examining the roots of modern dialects, it investigates whether they are evolved forms of Classical Arabic or extensions of Ancient Arabic, reaching into broader Semitic languages. Methods: Researchers collected samples that are common of the dialectal phenomena in the Jordanian dialect, selected specific ones to look up their origin in the principal linguistic sources, and studied each phenomenon in dependently. Results: The study found that modern dialects are an extension of ancient ones, which are linguistic patterns coexisting with Classical Arabic, which is considered one of these dialects, thus, Classical Arabic received different attention than other dialects from its speakers, for economic, religious, and political aspects, and, therefore, dominated other dialects, and became the origin that others follow. The research also found that Ancient Arabic language had several levels, standard and colloquial, and not one level as some researchers come to think. Conclusions: This research challenges the notion that modern dialects evolved from Classical Arabic, asserting that they coexisted with Ancient Arabic rather than being its evolved form. It contends that dialects will persist alongside Classical Arabic without posing a threat to it. Additionally, the study examines the ancient language on two levels: a high eloquent level represented by preserved poetic models, and a dialectal level evidenced by prevailing patterns in the past.